BES1 directly binds to the promoter of the ACC oxidase 1 gene to regulate gravitropic response in the roots of Arabidopsis thaliana. (2nd January 2020) - Park, Chan-Ho; Seo, Chaiweon; Park, Yeon Ju; Youn, Ji-Hyun; Roh, Jeehee; Moon, Jinyoung; Kim, Seong-Ki
ABSTRACT: Brassinosteroids (BRs) are known to be endogenous regulators of ethylene production, suggesting that some BR activity in plant growth and development is associated with ethylene. Here, we demonstrated that ethylene production in Arabidopsis thaliana roots is increased by BR signaling via the ethylene biosynthetic gene for ACC oxidase 1 ( ACO1 ). Electrophoretic mobility shift and chromatin immune-precipitation assays showed that the BR transcription factor BES1 directly binds to two E-box sequences located in the intergenic region of ACO1 . GUS expression using site mutations of the E-box sequences verified that ACO1 is normally expressed only when BES1 binds to the E-boxes in the putative promoter of ACO1, indicating that this binding is essential for ACO1 expression and the subsequent production of ethylene in A. thaliana roots. BR exogenously applied to A. thaliana roots enhanced the gravitropic response. Additionally, bes1-D exhibited a greater gravitropic response than did the wild-type specimens, proving that BR is a positive regulator of the gravitropic response in A. thaliana roots. The knock-down mutant aco1-1 showed a slightly lower gravitropic response than did the wild-type specimens, while bes1-D X aco1-1 exhibited a lower gravitropic response than did bes1-D. Therefore, ACO1 is a direct downstream target for BR transcription factor BES1, which controls ethylene production for gravitropism in A. thaliana roots.